ENERGY EFFICIENCY AND ASSESSMENT METHODS OF TECHNOLOGICAL SYSTEMS OF WATER SUPPLY AND WATER DISPOSAL - A. A. Kapansky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2016)
The existing methods for assessing the energy efficiency of technological systems of water supply and water disposal are examined. The main tool of the existing methods is a settlement-and-analytical method, and, in accordance with the mentioned one, the determining of general and specific electric power consumption is based on actual consumption evaluation, evaluation of pressure and efficiency of the pump unit. However, in practical terms a lot of factors influence on those characteristics therefore affecting the resulting magnitude of energy efficiency and leading to errors in the calculation. These factors include the technical condition of the equipment and piping systems, alterations in the modes of operation of pumping units over time, a significant impact of the ambient temperature on the power consumption, amount of precipitation and the chemical composition of the effluent. As an object of management water supply and water disposal systems are considered as a totality; therefore the assessment of the energy efficiency of pipeline enterprises ought to be based on a systematic approach, whereas the existing methods are mainly based on an analysis of operating modes of individual electrical equipment, not on the whole technological system. The article describes the management system of energy efficiency of pipeline water supply and water disposal systems. The management system is based on information base of statistic data of power, hydraulic and industrial indexes of wastewater management. The original basic mathematical models of common costs and unit costs of electrical power in the water supply and water disposal systems, which are the basis for the solution of the problems of forecasting and the current state assessment of energy efficiency of enterprises, the selection of priority areas of energy efficiency and finding the ways to save energy resources, are presented.